Oleogelation of sunflower-linseed oils with carnauba wax as an innovative strategy for shortening substitution in cakes - Roufegarinejad, Leila; Dehghani, Shabnam; Bakhshi, Simin; Toker, Omer Said; Pirouzian, Haniyeh Rasouli; Khiabani, Arezou Habibzadeh (ELSEVIER SCI LTD, 2024)
The aim of this study was to fabricate a carnauba wax oleogel with improved nutritional characteristics including reduced omega 6:omega 3 ratio and heightened alpha-linolenic acid through sunflower (SO): linseed oil (LO) in various ratios (100:0, 80:20, 70:30, 50:50, 30:70, 20:80, and 0:100 %), for potential shortening substitution in cakes. Combining LO with SO up to 50 % improved oleogel properties considering intra- or intermolecular hydrogen bonding and crystallinity. These oleogels had similar thermal behavior and better morphological structure than oleogel prepared exclusively with SO (100 SO), with reasonable oil binding capacity and oxidation stability. Moreover, 50SO/50LO achieved reasonable omega 6:omega 3 ratio (1.49), and a healthier lipid profile compared to 100 SO (390.7). The prepared cakes with 70 % shortening substitution using oleogel were accepted in the sensory assay, and leads to a significant reduction in omega 6:omega 3 ratio (77.64 %), and lipid peroxidation (P < 0.05), so introduced as an optimal formulation for enhanced cake nutrition.
Keywords: Fatty acid profile; Linseed oil; Sunflower oil; Oleogel; omega 6:omega 3 ratio; ATR-FTIR SPECTROSCOPY; FAT; ADULTERATION; HAZELNUT; Chemistry; Food Science & Technology; Nutrition & Dietetics